ANALISIS FAKTOR YANG MEMPENGARUHI MINAT BELI KOSMETIK HALAL PADA MAHASISWA UNIVERSITAS DI JAMBI - Alya; Titin Agustin Nengsih; Elyanti Rosmanidar (STKIP Subang, 2026)
This study examines the influence of religiosity, halal logos, and knowledge on university students’ intention to purchase halal cosmetics in Jambi Province. Using a quantitative survey approach, data were collected from 100 students across five universities through purposive sampling. Multiple linear regression analysis with SPSS was applied after validity, reliability, and classical assumption tests. The findings reveal that religiosity and knowledge positively and significantly affect purchase intention, while the halal logo has no partial significant effect. Simultaneously, all variables significantly influence purchasing interest. These results indicate that students’ religious values and knowledge are key factors in shaping their intention to buy halal cosmetics.